Invitrogen 2001 catalogue. (Groningen, The Netherlands Invitrogen, 2000)
Introduces cloning and genetic engineering, exploring the technology and social issues involved and looking toward what the future might bring as it becomes possible to duplicate even human DNA.
Understanding the terms -- Learning through history -- Gene genies and clone arrangers -- What the future holds.
Includes index.
Keywords: Cloning -- Juvenile literature; Genetic engineering -- Juvenile literature; Cloning; Genetic engineering; Genetics